CRIMINAL LIABILITY FOR NOTARIES THOSE INVOLVED IN DOCUMENT FORGERY - Lestari, Fifi Ayu (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The purpose of writing this journal is to analyze and examine how criminal liability for Notaries involved in document forgery is viewed from a criminal law perspective and how criminal law provisions apply to Notaries involved in document forgery. Article 1 paragraph (1) of the Notary Law states that a Notary is a Public Official who is authorized to make authentic deeds and has other authorities as referred to in this Law or based on other Laws. Notaries obtain attributional authority from the State through the Notary Law, meaning that this authority is inherent in the Notary's Office. In carrying out their duties and positions, Notaries are generally assisted by Notary staff, in this case preparing everything needed to make authentic deeds. One of the documents that must be prepared by Notary staff is a letter. Notary staff only assists in carrying out their work. Responsibility for authentic deeds remains the responsibility of the Notary. If the Notary commits the crime of document forgery which results in defects in the authentic deed, it is possible that the Notary must be held responsible for this. Forgery of letters that occurs can occur due to the falsification of the contents of the letter or the falsification of the authority and the contents of the authority in the letter. Criminal liability for a Notary if proven to have committed the crime of forgery of letters is the crime of participation in the crime of forgery of letters contained in Article 55 Jo. Article 263 paragraph (1) and (2) of the Criminal Code or Article 264 or 266 of the Criminal Code, as well as Article 56 paragraph (1) and (2) Jo. Article 263 paragraph (1) and (2) of the Criminal Code or Article 264 and Article 266 of the Criminal Code, because the Notary is considered negligent in carrying out his duties and position.